Steve Jobs or no jobs? Entrepreneurial activity and performance among Danish college dropouts and graduates - Guido Bünstorf; Kristian Nielsen; Bram Timmermans (Philipps-University Marburg, School of Business and Economics, 2016)
Are college dropouts successful entrepreneurs? Other than anecdotal evidence on illustrious college dropouts who managed to become self-made billionaires, there is only limited empirical evidence to answer this question. This paper addresses this issue by investigating the relationship between college dropout or graduation and entrepreneurship activity as well as performance. Using information from the Danish labor market register, we identify college students, whether these students graduate, and if they registered a new venture. We find that a larger share of dropouts starts a business, but this reflects the endogeneity of the decision to exit from college. On average, becoming an entrepreneur does not allow dropouts to escape from their punishment in the labor market.
Keywords: L26; I29; 330; entrepreneurship; higher education; college dropouts; returns to entrepreneurship